Cognitive decline: A vitamin B perspective. (November 2016) - Mikkelsen, Kathleen; Stojanovska, Lily; Tangalakis, Kathy; Bosevski, Marijan; Apostolopoulos, Vasso
Highlights: High levels of homocysteine are noted in patients with cognitive decline, including dementia and Alzheimer's disease. Vitamin B supplementation has been shown to decrease homocysteine levels. Low levels of vitamin B (B1, B2, B6, B9, B12) are common in patients with cognitive decline, including dementia and Alzheimer's disease. Abstract: Cognitive decline is one of the major causes of disability in older people. A high level of homocysteine, a byproduct of vitamin B, has been linked to brain atrophy, which itself is a precursor to cognitive decline leading to dementia and Alzheimer's disease. In addition, a low level of vitamin B is often noted in patients with dementia and Alzheimer's disease and its supplementation has been shown to improve memory and to slow the progress of brain atrophy. This information may aid in the use of vitamin B as a preventative measure against severe cognitive decline, and thus reduce the onset of conditions such as dementia and Alzheimer's disease.